2023
DOI: 10.1097/qai.0000000000003114
|View full text |Cite
|
Sign up to set email alerts
|

Birth Country Influences the Choice of Antiretroviral Therapy in HIV-Infected Individuals: Experience From a French HIV Centre

Abstract: Objectives: To assess whether antiretroviral therapy (ART) prescriptions differ between naive and virally suppressed HIV patients born in France (PBFs) and in Sub-Saharan Africa (PBSSAs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…We also performed a sensitivity analysis restricting it to men, to eliminate the potential confounding effect of gender and pregnancy, and this analysis strengthened the result. These findings come as a confirmation to what was found in a previous smaller study by Palich et al [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also performed a sensitivity analysis restricting it to men, to eliminate the potential confounding effect of gender and pregnancy, and this analysis strengthened the result. These findings come as a confirmation to what was found in a previous smaller study by Palich et al [13].…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have highlighted inequalities in treatment based on race, driven by implicit bias among physicians [9][10][11][12]. Recent results from a French monocentric study showed that PWH born abroad may not receive similar first-line regimens as PWH born in France [13]. It should be mentioned that in France, health insurance is free of charge, including for undocumented individuals.…”
Section: Introductionmentioning
confidence: 99%
“…prescription of boosted-protease inhibitor-or integrase strand transfer inhibitor-containing ART). Indeed, the distribution of these classes suggested important differences in maintenance ART prescriptions by place of birth, as highlighted in previous studies among treatment-naive PWH [1][2][3].…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies have reported disparities in antiretroviral therapy (ART) prescribing in the United States [1] and France [2,3] as a first line based on race, ethnicity and/or country of birth. Non-White and foreign-born people with HIV (PWH) were less likely to receive integrase stand transfer inhibitor (INSTI)-containing regimens, or to receive them in the earliest calendar periods, than White and native people with HIV.…”
Section: Introductionmentioning
confidence: 99%